Fish feed formulation with immune-enhancer gras base for Asian seabass, Lates calcalrifer - Nazarudin, Muhammad Farhan; Idrus, E. S.; Shamsudin, Mariana Nor (2012)
In the rapid expanding activities of aquaculture, advancement in fish husbandry technologies is utmost important for sustainable productivity, the critical aspects is fish health management and disease prevention. To support this industry in maintaining global competitiveness, innovation in product formulation for fish health maintenance is the focus of the present research. The research ultimate aim is product development that supports commercially important fish production through improving fish health with cascading impact on the subsequent aquaculture determinants, environmentally-friendly feeds, more efficient feeding strategies to increase production efficiencies, decrease production cost from treatment expenses, improve product quality, and minimize environmental impact. The innovation in product formulation encompassed vaccine components and preparation for application in hatcheries or farms to protect fish from a serious and detrimental haemmorhagic disease, vibriosis. Substantial economic loss from vibriosis is a worldwide aquaculture phenomenon affecting livelihood and income of farmers.